Test-Retest Reliability and Physiological Responses Associated with the Steep Ramp Anaerobic Test in Patients with COPD - Robyn L. Chura; Darcy D. Marciniuk; Ron Clemens; Scotty J. Butcher (Pulmonary Medicine)
The Steep Ramp Anaerobic Test (SRAT) was developed as a clinical test of anaerobic leg muscle function for use in determining anaerobic power and in prescribing high-intensity interval exercise in patients with chronic heart failure and Chronic Obstructive Pulmonary Disease (COPD); however, neither the test-retest reliability nor the physiological qualities of this test have been reported. We therefore, assessed test-retest reliability of the SRAT and the physiological characteristics associated with the test in patients with COPD. 11 COPD patients (mean FEV1 43% predicted) performed a cardiopulmonary exercise test (CPET) on Day 1, and an SRAT and a 30-second Wingate anaerobic test (WAT) on each of Days 2 and 3. The SRAT showed a high degree of test-retest reliability (ICC=0.99; CV=3.8%, and bias 4.5 W, error −15.3–24.4 W). Power output on the SRAT was 157 W compared to 66 W on the CPET and 231 W on the WAT. Despite the differences in workload, patients exhibited similar metabolic and ventilatory responses between the three tests. Measures of ventilatory constraint correlated more strongly with the CPET than the WAT; however, physiological variables correlated more strongly with the WAT. The SRAT is a highly reliable test that better reflects physiological performance on a WAT power test despite a similar level of ventilatory constraint compared to CPET.